Pengaruh Pembelajaran IPS terhadap Kecerdasan Ekologis Siswa Kelas VII SMP - Anggi Saputri; Desy Safitri; Sujarwo Sujarwo (Departement of Mathematics Education, 2023)
Environmental problems are currently an issue of concern in the world of education. Therefore, every student must have ecological intelligence that can be formed through learning. One of them is through IPS learning. The purpose of this research was to determine whether there is an effect of social studies learning on students ecological intelligence. This type of research is quantitative research with a survey method through questionnaires and using a Likert scale. The sample of this research was 81 students using simple random sampling, namely taking samples from the population at random as a sample determination. The hypothesis testing was carried out with the help of SPSS Statistics 25. Based on the data analysis requirements test and the hypothesis testing that had been carried out, the resulting T test value was 15,661 > 1,665, meaning that H1 was accepted which